2019
DOI: 10.1002/mrm.28060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of retention of gadolinium by brain, bone, and blood following linear gadolinium‐based contrast agent administration in rats with experimental sepsis

Abstract: Purpose It is important to identify populations that may be vulnerable to the brain deposition of gadolinium (Gd) from MRI contrast agents. At intervals from 24 hours to 6 weeks following injection of a linear Gd contrast agent, the brain, blood and bone content of Gd were compared between control rats and those with experimental endotoxin‐induced sepsis that results in neuroinflammation and blood–brain barrier disruption. Methods Male rats were injected intraperitoneally with 10 mg/kg lipopolysaccharide. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Taken together, the mechanism and the relevance of REEs to health and disease in human body remain obscure. Rats are standard experimental animals for toxicological research for chemicals and are frequently used to observe the toxicological effects of trace elements [16][17][18]. Herein, the main purpose of the current study is to explore the accumulation characteristics of selected REEs in different tissues and organs, as well as the detoxification and elimination of high-dose REEs of Sprague-Dawley (SD) rats.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the mechanism and the relevance of REEs to health and disease in human body remain obscure. Rats are standard experimental animals for toxicological research for chemicals and are frequently used to observe the toxicological effects of trace elements [16][17][18]. Herein, the main purpose of the current study is to explore the accumulation characteristics of selected REEs in different tissues and organs, as well as the detoxification and elimination of high-dose REEs of Sprague-Dawley (SD) rats.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in bone retention persisted in the sepsis model and was significantly increased compared to controls up to 3 weeks, but by 6 weeks had reduced to levels comparable to those in sham groups given GBCAs, demonstrating a transient effect of sepsis on bone retention in this model. Although LPS and sham animals had equivalent bone gadolinium at 6 weeks, gadolinium was still detectable and did not show much clearance over time, although the mechanisms for this difference in retention are unknown (Damme et al 2020 ). This increased retention in the bone compared to other tissues has been hypothesised to be due to the bone serving as a reservoir or deep compartment for gadolinium, potentially resulting in the chronic and slow release of gadolinium over time as a result of the incorporation of gadolinium by osteoblasts into the bone matrix (Abraham et al 2008 ; Darrah et al 2009 ).…”
Section: Gadolinium Distribution In Humans and Animalsmentioning
confidence: 99%
“…Gadolinium-based contrast agents (GBCA) are commonly used clinical MRI contrast agents, but recent studies have shown that their biosafety cannot be guaranteed, for this type of contrast agent is associated with renal fibrosis and the nervous system deposition. 40 Thus, the development of new contrast agents is one of the ways to improve biosafety. Previous report about biosafety of iron oxide nanoparticle (IONP) underlined that the biological safety of IONP was significantly better than that of GBCA, especially it would not cause nephrogenic systemic fibrosis or had a long retention in vital organs.…”
Section: Discussionmentioning
confidence: 99%